Application of the life course paradigm to the study of financial solvency and financial satisfaction in later life: A comparative study of American and Dutch elderly consumers. Issue 4 (2nd October 2019) - Mathur, Anil; Kasper, Hans
ABSTRACT: Although several authorities on personal finance have suggested the need for studying a person's financial behaviour over his or her entire life course, their research efforts have been hampered by a lack of viable conceptual frameworks. The present study shows how researchers could employ the life course paradigm to study consumers' financial behaviours. It illustrates how researchers could derive hypotheses from theories dictated by the life course paradigm to explain financial solvency and financial satisfaction in later life. These hypotheses are tested using samples of individuals more than 60 years of age from the United States (N = 191) and the Netherlands (N = 173). Findings suggest that the overall life course framework can be used to understand financial solvency and financial satisfaction in later life. Implications for theory and further research using the life course approach are also discussed.